2016
DOI: 10.1242/jcs.185413
|View full text |Cite
|
Sign up to set email alerts
|

Scribble is required for pregnancy-induced alveologenesis in the adult mammary gland

Abstract: The cell polarity protein scribble (SCRIB) is a crucial regulator of polarization, cell migration and tumorigenesis. Whereas SCRIB is known to regulate early stages of mouse mammary gland development, its function in the adult gland is not known. Using an inducible RNA interference (RNAi) mouse model for downregulating SCRIB expression, we report an unexpected role for SCRIB as a positive regulator of cell proliferation during pregnancy-associated mammary alveologenesis. SCRIB was required in the epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
1
11
1
Order By: Relevance
“…Finally, lano knock-out mice are viable and fertile with a normal Mendelian distribution [80]. However, as in scribble and erbin-deficient mice [76,81,82], we observed a delay in the development of the mammary epithelium in these animals (unpublished observations).…”
Section: Role Of Lap Proteins In Cancersupporting
confidence: 57%
“…Finally, lano knock-out mice are viable and fertile with a normal Mendelian distribution [80]. However, as in scribble and erbin-deficient mice [76,81,82], we observed a delay in the development of the mammary epithelium in these animals (unpublished observations).…”
Section: Role Of Lap Proteins In Cancersupporting
confidence: 57%
“…To investigate the possible molecular mechanisms underlying the reduced STAT5 activation observed upon Rab6a deletion, we took advantage of T47-D, a human breast cancer-derived cell line commonly used for studying PRL-induced signaling events ( Johnson et al, 2010 ; Baker et al, 2016 ; Oakes et al, 2017 ). Double staining for RAB6 and GM130 confirmed the expected localization of RAB6 in the Golgi of T47-D cells ( …”
Section: Resultsmentioning
confidence: 99%
“…Studies on PRLR signaling in the mouse mammary gland have been hampered by the lack of reliable antibodies working in immunohistochemistry, immunocytochemistry or immunoblotting ( Brisken and Ataca, 2015 ). To circumvent this difficulty, we used the well-characterized PRL-responding human T47-D cells ( Johnson et al, 2010 ; Baker et al, 2016 ; Oakes et al, 2017 ). Using siRNAs, we found that RAB6A depletion in this model resulted in decreased PRLR levels, altered membrane expression and reduced STAT5 activation downstream of PRL action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations